Muppet Treasure Island [videorecording (DVD)] - Stevenson, Robert Louis, 1850-1894 (Walt Disney Home Entertainment : distributed by Buena Vista Home Entertainment, 2005)
When young Billy comes to possess a secret treasure map, he sets sail with mild-mannered Capt. Smollet and a host of assorted Muppets and humans in search of the wealth. Their adventure is filled with songs, wacky humor, and irreverent silliness.